The Dynamics of Uang Panai' in Makassar City After the Fatwa of MUI of South Sulawesi No. 2 Year 2022: Measuring Sharia Compliance and Preservation of Tradition - Nasmi, Nasmi; Bakry, Muammar; Haddade, Abdul Wahid; Salam, Abdul (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This research aims to determine the effect of the MUI South Sulawesi fatwa No. 2 of 2022 concerning uang panai' and its implications on Bugis tribal marriages in Bangkala Village, Manggala District, Makassar City. The main problem in this study is related to the philosophical basis of uang panai’, the position of dowry money in the Bugis ethnic community in Bangkala Village, Manggala District, Makassar City and the influence of the South Sulawesi MUI fatwa No. 2 of 2022 concerning uang panai on Bugis ethnic marriages in Bangkala Village, Manggala District, Makassar City. In general, this study discusses the Indonesian Ulema Council (MUI) of South Sulawesi has issued a fatwa on uang panai which must be considered carefully and properly by the community, especially in South Sulawesi so that there is no misunderstanding among the commu nity regarding the meaning of uang panai’. The researcher found that giving uang panai’ according to the South Sulawesi MUI is a permissible custom (mubah) if it does not violate sharia principles. Then its legal status can change to haram if it violates sharia principles. This research is a field research with a sociological approach and a socio-cultural approach. The results of this research indicate that the MUI South Sulawesi fatwah on dowry has not had an impact or influence on the community, especially in the Bangkala Village, Manggala District, Makassar City, due to the lack of education and socialization by related parties. In fact, this MUI fatwa is here to answer and be a solution to the problem of high dowry in the community.